DESIGN AND IMPLEMENTATION OF ANDROID AND GPS BASED FRIEND APPLICATION IN MITIGATION EFFORTS AND EARLY EMERGENCY AID FOR DISASTER VICTIMS IN MATERNAL AND NEONATAL PARENTS - Munthe, Juliana; Sinaga, Siti Nurmawan; Manurung, Herna Rinayanti; Sinuhaji, Lidya Natalia Br; Manurung, Indra (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2025)
According to BNBP data (2022), Indonesia experienced 3,544 disasters consisting of 1,531 floods, 1,068 extreme weather events, 634 landslides, 252 forest and land fires, 28 earthquakes, 26 extreme waves and abrasion, 4 droughts, and 1 volcanic eruption. A total of 6,144,324 people suffered and were displaced, 861 people died, 46 people were missing, and 8,727 people were injured as a result of the disaster in 2022. The purpose of this study is an application that simplifies the reporting system process using the maternal and neonatal emergency response application. The problem analysis process in this study uses a fishbone diagram to identify problems and system design using UML diagrams consisting of use cases, activity diagrams, and sequence diagrams. The results of this study make it easier for the public to get information about disaster-prone areas and disaster reporting. In addition to the community side, this application is useful for health workers and regional disaster management agencies in the process of reporting activities while in the field. This application is tested using the black box testing method.